Technical Factors Affecting to Durian (Durio Zibethinus Murr) Drink Production - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2018)
Durian (Durio Zibethinus Murr) fruit possesses high nutritional value and has rich bioactive properties. The ripe durian fruit has unique taste and aroma. It is usually used for fresh consumption. During the durian havesting season, excessive supply of the fruit causes the price of durian decreasing dramatically. Therefore we have our tried to add value to the durian fruit. One method of adding value to fresh durian is processing it into drink. We carried out the investigation of extraction (ratio of water: durian, temperature and time of blanching); juicy mixture; preservation. Our result showed that the durian drink having the best quality when extracting with water: durian pulp ratio (70:30) at 85 oC in 3 minutes. The sample was then cooled to 37°C before the addition of pectinase enzyme at 0.06%. The juice was then incubated in a water bath at 37°C in 45 minutes. After the incubation process, the juice was heated in a water bath at 100°C for 2 minutes to inactivate all enzymes present. The hydrolyzed durian juice will be formulated with sugar 2%, citric acid 6%, gellan gum 0.03%. Durian drink shelf-life could be maintained for 12 months.Keywords: Durian, Durio zibethinus Murr, Drink, Gellan gum, Pectinase, Shelf-life.